A Dual Fluorescence–Spin Label Probe for Visualization and Quantification of Target Molecules in Tissue by Multiplexed FLIM–EPR Spectroscopy. Issue 27 (26th May 2021) - Dong, Pin; Stellmacher, Johannes; Bouchet, Lydia M.; Nieke, Marius; Kumar, Amit; Osorio‐Blanco, Ernesto R.; Nagel, Gregor; Lohan, Silke B.; Teutloff, Christian; Patzelt, Alexa; Schäfer‐Korting, Monika; Calderón, Marcelo; et al.
Abstract: Simultaneous visualization and concentration quantification of molecules in biological tissue is an important though challenging goal. The advantages of fluorescence lifetime imaging microscopy (FLIM) for visualization, and electron paramagnetic resonance (EPR) spectroscopy for quantification are complementary. Their combination in a multiplexed approach promises a successful but ambitious strategy because of spin label‐mediated fluorescence quenching. Here, we solved this problem and present the molecular design of a dual label (DL) compound comprising a highly fluorescent dye together with an EPR spin probe, which also renders the fluorescence lifetime to be concentration sensitive. The DL can easily be coupled to the biomolecule of choice, enabling in vivo and in vitro applications. This novel approach paves the way for elegant studies ranging from fundamental biological investigations to preclinical drug research, as shown in proof‐of‐principle penetration experiments in human skin ex vivo. Abstract : A novel multi‐label synthetic platform for a functional dual fluorescence–spin label probe enables the non‐destructive simultaneous quantification and visualization of molecules in biological tissue. Multiplexed FLIM and EPR spectroscopy avoids analytical inconsistencies between both techniques. Beside tissue applications, molecular spectroscopic studies of biomolecular conformation, structure, dynamics, and microenvironment are feasible.